ANALISA PERBANDINGAN METODE FILTER GAUSSIAN, MEAN DAN MEDIAN TERHADAP REDUKSI NOISE - Andre Wedianto; Herlina Latipa Sari; Yanolanda Suzantri H (UNIVED Press, 2016)
This study aimed to compare the Gaussian Method, Mean and Median in performing noise reduction using the programming language Matlab. Can make improvements in particular digital image noise reduction. Limitation of the study is a programming language used to build applications of digital image processing, especially the reduction of noise in this research Matlab programming. Digital image used jpeg extension. The method used method of Gaussian, Mean and Median. Initial image or the input image is an image that is damaged due to disturbances in image noise and generate output * .jpg. Results of the study was the result of improved image noise, especially against tampering methods used method of Gaussian, Mean and Median, of the three methods are used equally well, because all three of these methods can improve the existing noise disturbance. In doing repairs noise on digital images to note the type of interference and a good method to use. The resulting image of this improvement is relatively equal in terms of both the pixel size and the amount of file.Keywords: Gaussian, Mean and Median